Natural transitions of non-high-density lipoprotein cholesterol levels in children 9-11 years of age - Meng, Yaxing; Kidokoro, Tetsuhiro; Imai, Natsuko; Thomson, Russell; Tomkinson, Grant R.; Magnussen, Costan G. (Elsevier, 2026)
Introduction:
Unites States guidelines recommend universal lipid screening in children between ages 9–11 years, with follow-up screening at ages 17–21 years. Non-high-density lipoprotein-cholesterol (non-HDL-C) is the preferred marker. However, the stability of non-HDL-C within the screening window remains unclear. This study aimed to estimate the probabilities of non-HDL-C transitioning between its classifications (acceptable, borderline-high, and high) during the 9–11-year age period and the average duration it remains stable within each classification.
Methods:
This study included 496 Japanese children with non-HDL-C measured between ages 9 and 11 years. Data were collected from 2015 to 2019, and analyses were conducted in 2024. A time-homogeneous continuous-time Markov model was used to estimate the probabilities of transitioning among non-HDL-C classifications—acceptable (<120 mg/dL), borderline-high (120-144 mg/dL), and high (≥145 mg/dL)—and the average duration children remained in a given non-HDL-C classification before transitioning.
Results:
At the population level, all non-HDL-C classifications identified at age 9 years were estimated to remain stable for more than two years. Children with acceptable non-HDL-C had a mean duration of 10.6 years (95% confidence interval: 7.8-14.5) before transitioning to another classification, with an estimated 0.90 probability of maintaining in the acceptable classification during the 9–11-year window.
Conclusions:
Non-HDL-C classifications identified at age 9 years remained stable for over two years, supporting the appropriateness of screening at any point within the 9–11-year window. These findings offer insights into optimal lipid screening practices, thereby enhancing early cardiovascular disease prevention.